PENENTUAN PARAMETER GELOMBANG LAUT BERDASARKAN DATA ANGIN YANG MENGACU PADA ECMWF (EUROPEAN CENTRE FOR MEDIUM-RANGE WEATHER FORECAST) DIPERAIRAN DUSUN WAEYOHO, DESA KAWA, KAB. SBB - Saharti; Lilipory, Isak; Pattiselanno, Steanly R. R. (Jurusan Teknik Sipil, 2024)
In West Seram Regency, precisely in Waeyoho Hamlet, Kawa Village, which has an area of ​​20 hectares / 0.2 Km2 with a coastline length of 2 Km, is one of the places where most of the people earn their income from sea products (fishermen), where when they go out in the morning or in the afternoon then we will return to land the next day. Seeing this situation, when we are going to carry out shipping activities, of course, we need daily weather information such as wave height from strong winds that occur in the middle of the sea. Prediction of wave parameters using the wind data approach method taken from ECMWF (European Center for Medium-range Weather Forecast) data. Wind data obtained at the research location in the waters of Waeyoho Hamlet, Kawa Village, Sbb Regency, Maluku in 2023 throughout January - October has a dominant northwest wind direction with a wind speed of 11.10 m/s, based on the monthly wind speed graph. The highest wind speed was obtained in May, July, August, and September, the relationship between wind speed on land and at sea was obtained by the value RL = 1.1 and the value Uw = 12.21 m/s, the wind stress factor (Ua) was obtained 15, 41 m/s, The average effective fetch value from the research location was 346.03 Km. Forecasting deep sea waves with limited fetch conditions, the value Hmo= 4.63m Tm=10.89 s, t=19.8 hours was obtained